Quantitation of Cytochromes b559, b6, and f, and the Core Component of Photosystem I P700 in Cyanobacterial Cells - Motohide Aoki; Mikio Tsuzuki; Norihiro Sato (Bio-Protocol, 2016)
Cytochrome (Cyt) b559, an important and essential core component of photosystem II in the photosynthetic electron transport system, is a heme-bridged heterodimer protein composed of an alpha subunit (PsbE) and a beta subunit (PsbE), and its reduced form has an absorption maximum in the α-band at 559 nm. The amounts of Cyt b559 can be determined by spectrophotometrical measurement of reduced minus oxidized difference spectra that are normalized with absorbance of isosbestic point at 580 nm. The authors use differential extinction coefficients of Cyt b559 [Δε(559-580 nm) = 15.5 mM-1·cm-1], which have been reported by Garewal and Wasserman (1974). In addition to the Cyt b559, this procedure can be used for quantitation of Cyt b6 and Cyt f, the subunits of the Cyt b6/f complex, and P700, one of the core components of photosystem I. This protocol, which is adapted from Fujita and Murakami (1987), is used in a cyanobacterium, Synechococcus elongatus PCC 7942, and also in other cyanobacterial strains including Synechocystis sp. PCC 6803.